A polythiophene derivative photoelectric material and a preparation method and application thereof

CN116903830BActive Publication Date: 2026-11-03GUANGZHOU UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310499614.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-05
Publication Date
2026-11-03
Estimated Expiration
2043-05-05

AI Technical Summary

Technical Problem

Existing polythiophene derivative optoelectronic materials in all-polymer solar cells suffer from problems such as high HOMO energy levels, excessive crystallinity due to increased thiophene content, and poor solubility, which affect photoelectric conversion efficiency.

Method used

By simultaneously introducing two different electron-withdrawing groups at the β-position of monothiophene, a polythiophene derivative optoelectronic material with a thiophene-ethylene-thiophene-π-conjugated structure is prepared via Stille coupling polycondensation. This process modulates the energy level and reduces the thiophene content, avoiding excessive crystallization and poor solubility.

Benefits of technology

High photoelectric conversion efficiency of polymer solar cells was achieved by reducing the HOMO energy level and improving solubility, thereby reducing the thiophene content and improving device performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116903830B_ABST
    Figure CN116903830B_ABST
Patent Text Reader

Abstract

The application discloses a polythiophene derivative photoelectric material and a preparation method and application thereof. The material has a structure of formula I, has a unit structure of a thiophene-vinyl-thiophene-pi-conjugated structure group, two different electron-withdrawing groups are introduced at the beta position of the monothiophene at the same time, energy levels are adjusted, and negative effects caused by introduction of excessive content of thiophene on crystallization and solubility of the polymer are avoided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of materials technology, and in particular to a polythiophene derivative optoelectronic material, its preparation method, and its application. Background Technology

[0002] In recent years, all-polymer solar cells (All-PSCs) have attracted considerable attention due to their excellent flexibility, stretchability, and thermal stability. Thanks to the development of polymeric small molecule acceptors (PSMAs) strategies, the power conversion efficiency (PCE) of All-PSCs has exceeded 16%. However, the complex synthesis and high production cost of high-performance organic photovoltaic materials severely restrict the large-scale industrial production of organic photovoltaics. The most efficient polymer donors are conjugated polymers with alternating electron-rich and electron-deficient structural units. These structural units have fused ring structures, which are complex to synthesize, resulting in high production costs for the resulting polymers. Therefore, there is an urgent need for low-cost but high-performance polymer photovoltaic materials to achieve the large-scale manufacturing of PSCs.

[0003] Polythiophenes and their derivatives (PT) are considered the most promising candidates for large-scale, low-cost synthesis due to their simple chemical structures and readily available, inexpensive raw materials. Recent attention has focused primarily on improving the performance of polymer donor-small molecule acceptor blends, achieving PCEs of up to 17%. However, less attention has been paid to PT-based All-PSCs, resulting in relatively slow progress in PCEs, typically below 8%.

[0004] Due to the electron-donating properties of thiophene units, polythiophene and its derivatives possess relatively high HOMO energy levels, resulting in lower open-circuit voltages (V0.05) in solar cell devices fabricated with acceptor materials. OC Generally, introducing suitable electron-withdrawing groups at the β-position of thiophene is considered an effective strategy to lower the HOMO level, thereby increasing the Vo of the device. OC This is to improve the photoelectric conversion efficiency of the device.

[0005] The introduction of different electron-withdrawing groups can synergistically modulate the energy levels and morphology of materials. Typically, different electron-withdrawing groups are introduced simultaneously into the polymer backbone and side chains, but this increases the thiophene content in the polymer. However, an increased thiophene content is detrimental to lowering the HOMO energy level. Furthermore, increased thiophene content leads to an excessive tendency for polymer crystallization / aggregation, thus affecting the blending of the polymer donor and acceptor.

[0006] To realize high-performance polymer solar cells based on PTs donors, issues such as the high HOMO energy level of PTs, their strong π-π stacking, and crystallinity need to be addressed. Summary of the Invention

[0007] The present invention aims to at least solve one of the aforementioned technical problems existing in the prior art. Therefore, the object of the present invention is to provide a polythiophene derivative optoelectronic material, its preparation method, and its application. This material has a unit structure of thiophene-ethylene-thiophene-π-conjugated structural groups, wherein two different electron-withdrawing groups are simultaneously introduced at the β-position of the monothiophene group to adjust the energy level while avoiding the negative impact of introducing excessive thiophene on the crystallinity and solubility of the polymer.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0009] According to the first invention of the present invention, a compound of formula I or a salt thereof is provided:

[0010]

[0011] Wherein, R is selected from straight-chain alkyl, vinyl-containing straight-chain alkyl, branched alkyl, silyl chain, ester chain, ether chain, thioether chain, and polyethylene glycol chain.

[0012] Includes π-conjugated structural groups;

[0013] X is selected from hydrogen atom, halogen atom, and cyano group;

[0014] n is a natural number between 1 and 5000.

[0015] In some embodiments of the present invention, R is selected from any of the following groups:

[0016]

[0017] Where m is selected from natural numbers between 1 and 20; the dashed line indicates the connection position.

[0018] In some embodiments of the present invention, the π-conjugated structural group is selected from any one of the following groups:

[0019]

[0020]

[0021]

[0022] Wherein, R1 is selected from hydrogen atoms or alkyl groups; the dashed line indicates the connection position. Preferably, the alkyl group is selected from...

[0023]

[0024] In some embodiments of the present invention, X is selected from any one of F, Cl, Br, I, and cyano.

[0025] In some embodiments of the present invention, n is selected from natural numbers between 100 and 3000; preferably, it is a natural number between 500 and 2500; more preferably, it is a natural number between 800 and 2000.

[0026] In some embodiments of the present invention, the compound of formula I is selected from any one of the following compounds:

[0027]

[0028]

[0029] According to a second aspect of the present invention, a method for preparing a compound of formula I is provided, comprising the following steps:

[0030]

[0031] Compound I was prepared by Stille coupling polycondensation of compound Ih and compound Ii.

[0032] Among them, R, X, The definition of n is as described above.

[0033] In some embodiments of the present invention, the catalyst used for the Stille coupling polycondensation is a transition metal catalyst.

[0034] In some embodiments of the present invention, the transition metal catalyst is any one of Pd(acac)2, Pd(OAc)2, PdCl2, Pd(PPh3)2Cl2, Pd(dppf)Cl2, Pd2(dba)3, Pd(TFA)2, Pd2(allyl)2Cl2, Ni(COD)2, and NiCl2(PCy3)2.

[0035] In some embodiments of the present invention, the organic solvent used for the Stille coupling polycondensation is any one of toluene, tetrahydrofuran, diethyl ether, N,N-dimethylformamide, acetonitrile, methyl tert-butyl ether, n-heptane, isopropanol, or ethylene glycol dimethyl ether.

[0036] In some embodiments of the present invention, the Stille coupling polycondensation uses a phosphorus ligand; preferably, the phosphorus ligand is selected from at least one of tris(o-methylphenyl)phosphine, 2-(di-tert-butylphosphine)biphenyl and tris(2-furanyl)phosphine.

[0037] In some embodiments of the present invention, the Stille coupling polymerization is carried out under microwave or oil bath conditions.

[0038] In some embodiments of the present invention, the method for preparing the compound of formula I includes the following steps:

[0039]

[0040] (1) Compound Ib is prepared by reacting compound Ia with tert-butyllithium and then treating it with propyl chloroformate.

[0041] (2) Compound Ib was prepared by treating compound Ib with tetra-n-butylammonium fluoride;

[0042] (3) Compound Ic was treated with hexamethyldisiloxane and dibromo-1,1,2,2-tetrachloroethane to obtain compound Id; compound Id was hydrolyzed to obtain compound Ie.

[0043] (4) The compound of formula Ie was esterified by coupling agent 1,3-dicyclohexylcarbodiimide and catalyst 4-dimethylaminopyridine to obtain compound of formula If-1.

[0044] (5) Compound If-1 was synthesized by Stille coupling with (E)-1,2-bis(tributyltin)ethylene to obtain compound Ig-1;

[0045] (6) Compound of formula Ih-1 was prepared by treating compound of formula Ig-1 with trifluoroacetic acid and N-bromosuccinimide;

[0046] (7) Compound I-1 is prepared by Stille coupling polycondensation of compound Ih-1 and compound Ii.

[0047] According to a third aspect of the invention, a composition is provided comprising a compound of formula I dissolved or dispersed in a liquid medium.

[0048] In some embodiments of the present invention, the liquid medium includes water or an organic solvent.

[0049] In some embodiments of the invention, examples of the organic solvents include petroleum ethers; acetonitrile; aromatic hydrocarbons such as benzene, toluene, xylene, and 1,3,5-trimethylbenzene; ketones such as acetone and methyl ethyl ketone; ethers such as tetrahydrofuran, dialkyl, bis(2-methoxyethyl) ether, diethyl ether, diisopropyl ether, and tert-butyl methyl ether; alcohols such as methanol, ethanol, butanol, and isopropanol; aliphatic hydrocarbons such as hexane; acetate esters such as methyl acetate, ethyl acetate, methyl formate, ethyl formate, isopropyl acetate, and butyl acetate; halogenated aliphatic and aromatic hydrocarbons such as dichloromethane, chloroform, vinyl chloride, chlorobenzene, dichlorobenzene, and trichlorobenzene; and cyclic solvents such as cyclopentanone, cyclohexanone, and 2-methylpyrrolidone.

[0050] In some embodiments of the present invention, when R is selected from... When, the compound of formula Ia reacts with a compound selected from... After reacting any one of the compounds in Ni(dppp)Cl2 and anhydrous diethyl ether, magnesium metal and anhydrous ethanol are added to continue the reaction, yielding the compound. Following the aforementioned synthetic method, the compound The Stille coupling reaction and subsequent related reactions (steps (5) to (7) above) can be carried out to obtain the compound of formula I corresponding to the R substituent.

[0051] In some embodiments of the present invention, when R is selected from... At that time, round-bottom flasks A and B were evacuated using a vacuum system, and then refilled with nitrogen to remove moisture and air from the flasks. Then, a magnesium strip and anhydrous diethyl ether were placed in flask A, and a compound of formula Ia, Ni(dppp)Cl2, and anhydrous diethyl ether were placed in flask B. Then, a mixture selected from... Stir at 15–35°C for 1–3 hours. Then, transfer the solution from flask A to flask B and stir at room temperature for 8–12 hours. Stop the reaction by adding dilute hydrochloric acid to flask B, and extract with diethyl ether and distilled water. Collect the organic layer, dry it with anhydrous magnesium sulfate, and filter it through filter paper. Collect the filtrate and remove the diethyl ether using a rotary evaporator. Finally, purify the condensed mixture by distillation under reduced pressure to obtain a colorless oily substance, i.e., the compound.

[0052] In some embodiments of the present invention, when R is selected from... When, the compound of formula Ia reacts with a compound selected from... Any one of the reactions can be used to prepare a compound. Following the aforementioned synthetic method, the compound The Stille coupling reaction and subsequent related reactions (steps (5) to (7) above) can be carried out to obtain the compound of formula I corresponding to the R substituent.

[0053] In some embodiments of the present invention, when R is selected from... Add n-butyllithium to the diethyl ether solution of compound Ia, stir at -85℃ to -70℃ for 1 to 2 hours, and then add a mixture selected from... After stirring for 2–4 hours, the reaction mixture was heated to room temperature and then poured into a saturated NH4Cl solution. The aqueous layer was extracted 2–3 times with diethyl ether. The combined organic layers were washed with brine, dried over anhydrous Na2SO4, and concentrated under vacuum. The residue was purified by silica gel (n-hexane) column chromatography to obtain the compound.

[0054] In some embodiments of the present invention, when R is selected from... When, the compound of formula Ia reacts with The reaction yields the compound. Following the aforementioned synthetic method, the compound The Stille coupling reaction and subsequent related reactions (steps (5) to (7) above) can be carried out to obtain the compound of formula I corresponding to the R substituent.

[0055] In some embodiments of the present invention, when R is selected from... Anhydrous tetrahydrofuran was then injected into a three-necked flask, which was then placed in an ice-water bath and magnetically stirred. The mixture was then added sequentially. or Potassium iodide and sodium hydride were dissolved. The solution of compound Ia dissolved in tetrahydrofuran was slowly added dropwise to the reaction apparatus over 40–70 min using a constant-pressure separatory funnel. The reaction apparatus was then transferred to an oil bath and reacted under nitrogen protection at 40–60 °C with continuous stirring for 8–12 h. After cooling to room temperature, an appropriate amount of distilled water was added, and the mixture was extracted 2–3 times with ethyl acetate. The separated organic phase was washed 2–3 times with saturated brine, dried over anhydrous Na₂SO₄, and filtered. The solvent was removed by rotary evaporation, and the crude product was purified by silica gel column chromatography to obtain the compound.

[0056] According to a fourth aspect of the invention, a thin-film semiconductor is provided, comprising the compound of formula I.

[0057] According to a fifth aspect of the invention, a composite is provided, comprising a substrate and a thin-film semiconductor deposited on said substrate.

[0058] According to a sixth aspect of the present invention, a field-effect transistor device is provided, comprising the thin-film semiconductor or the composite thereof.

[0059] According to a seventh aspect of the present invention, a photovoltaic device is provided, comprising the thin-film semiconductor or the composite described herein.

[0060] In some embodiments of the present invention, the photovoltaic device includes a solar cell.

[0061] According to an eighth aspect of the present invention, an organic light-emitting device is provided, comprising the thin-film semiconductor or the composite.

[0062] The beneficial effects of this invention are:

[0063] 1. The compound of formula I provided by this invention is a photovoltaic material based on polythiophene ethylene derivatives. Due to the introduction of strong electron-withdrawing groups such as F, Cl, and CN, the monomer exhibits stronger electronegativity, resulting in photovoltaic materials derived from polythiophene ethylene derivatives with lower molecular orbital energy levels and good air stability. Among various electron-withdrawing groups, the F atom is one of the most feasible choices for lowering the energy level without introducing unnecessary steric hindrance. Furthermore, the introduction of the F atom can form intramolecular non-covalent interactions, improve molecular planarity, and increase intramolecular and intermolecular interactions, which is beneficial for improving carrier mobility and the photoelectric conversion efficiency of organic solar cells.

[0064] 2. This invention achieves control over polymer energy levels, solubility, aggregation, and crystallinity by simultaneously introducing two different electron-withdrawing groups at the β-position of a single thiophene group, thereby lowering the HOMO energy level of the polymer and reducing the proportion of thiophene in the polymer. The synergistic effect of the two electron-withdrawing groups is beneficial to further improving the performance of polymer solar cells. For example, the interaction between F and ester groups triggers intra- and inter-chain non-covalent interactions, increasing the planarity of the main chain and inter-chain charge transport. The vinyl bridge gives the resulting PT good solubility, high mobility, and strong solution pre-aggregation.

[0065] 3. The polythiophene ethylene derivative prepared by the present invention, which is copolymerized with vinyl-bridged R and X-substituted monothiophene and π-conjugated structure, has a deeper HOMO energy level and appropriate aggregation. When finally applied to all polymer solar cells, it achieves excellent photoelectric conversion performance.

[0066] 4. The compound of Formula I of the present invention not only introduces functionalized thiophene units to adjust the energy level and morphology of the polymer, but also reduces the thiophene content in the polymer to avoid its excessive crystallization and aggregation, thereby preventing it from affecting the performance of solar cell devices prepared based on the material. Attached Figure Description

[0067] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of compound 6 in Example 1 of the present invention.

[0068] Figure 2 This is the carbon NMR spectrum of compound 6 in Example 1 of the present invention.

[0069] Figure 3 This is the hydrogen nuclear magnetic resonance spectrum of compound 7 in Example 1 of the present invention.

[0070] Figure 4 This is the carbon NMR spectrum of compound 7 in Example 1 of the present invention.

[0071] Figure 5 This is a high-resolution mass spectrum of compound 7 from Example 1 of the present invention.

[0072] Figure 6 This is the hydrogen nuclear magnetic resonance spectrum of compound 8 in Example 1 of the present invention.

[0073] Figure 7 This is the carbon NMR spectrum of compound 8 in Example 1 of the present invention.

[0074] Figure 8 This is the nuclear magnetic resonance fluorine spectrum of compound 8 in Example 1 of the present invention.

[0075] Figure 9 This is a high-resolution mass spectrum of compound 8 from Example 1 of the present invention.

[0076] Figure 10 The absorption spectrum of polymer PFETVT-T in Experimental Example 1 of this invention is shown.

[0077] Figure 11 This is a cyclic voltammogram of the polymer PFETVT-T used in Experimental Example 1 of this invention for electrochemical testing.

[0078] Figure 12 The thermogravimetric analysis curves of polymers PFETVT-T and PETVT-FT in Experimental Example 1 of this invention are shown.

[0079] Figure 13 The images shown are atomic force electron microscopy (AFM) images and transmission electron microscopy (TEM) images of the PFETVT-T:L15 and PETVT-FT:L15 blend films in Experimental Example 2 of this invention.

[0080] Figure 14 The graphs (a) and (b) show the current-voltage curves and external quantum efficiency of the solar cell using polymer PFETVT-T and PETVT-FT as donor materials in Example 5 of this invention. Detailed Implementation

[0081] The present invention will be further described in detail below through specific embodiments. Unless otherwise specified, the raw materials, reagents, or apparatus used in the embodiments and comparative examples are all available from conventional commercial sources or can be obtained by existing technical methods. Unless otherwise specified, the test or experimental methods are conventional methods in the art.

[0082] In this invention, all basic reagents and chemicals are readily available and, unless otherwise specified, undergo further purification before use. Anhydrous toluene is prepared by treatment with metallic sodium. Unless otherwise specified, all reactions are carried out under a protective gas atmosphere. NMR spectroscopy was performed using a Bruker 400MHz NMR spectrometer. High-resolution spectroscopy was performed using a ThermoScientific™ Q-Exactive instrument from Thermo Scientific. Molecular weight determination was performed using a high-temperature GPC (Agilent PL-GPC220). UV spectroscopy was performed using a Shimadzu UV-3600 spectrometer. Cyclic voltammetry was performed using a CHI760 electrochemical workstation. Thermal analysis was performed using a STAReSystem. AFM testing was performed using an Asylum Research MFP-3D-Stand Alone instrument. TEM testing was performed using a TecnaiSpirit (20kV).

[0083] Example 1

[0084] This embodiment prepares a bromide monomer of a p-type organic semiconductor material having the structure shown in Formula I through the following steps:

[0085]

[0086] Step 1: Synthesis of Compound 2

[0087] Compound 1 (5.3 g, 16.4 mmol) was dissolved in anhydrous diethyl ether (200 mL). Lithium n-butyl (2.4 M, 7.2 mL, 1.05 eq) was added dropwise to the solution at -78 °C. After stirring at this temperature for 1 hour, propyl chloroformate was added, and the reaction mixture was then slowly heated to room temperature and stirred overnight. The reaction was quenched with water (30 mL), and the mixture was extracted with diethyl ether (3 × 40 mL). The combined organic layers were then washed with water (3 × 40 mL) and dried over anhydrous Na₂SO₄. After filtration to remove the solvent, the residue was purified by silica gel column chromatography using petroleum ether (PE):chloroform (CHCl₃) = 3:1 as the eluent to give compound 2 (4.0 g, yield = 73%) as a colorless liquid.

[0088] 1 H NMR (400MHz, CDCl3) h (ppm): 4.27 (t, J = 8.0 Hz, 2H), 1.80-1.78 (m, 2H), 1.03 (t, J = 8.0 Hz, 3H), 0.38 (s, 9H), 0.36 (s, 9H). 13C NMR (100MHz, CDCl3)h (ppm): 163.0 (d, J = 268Hz, CF), 162.72 (d, J = 5.0Hz, C = O), 154. 28,128.05(d,J=19.0Hz),122.09(d,J=31.0Hz),66.40,22.09,10.44,-0.68,-0.77. 19 F NMR (376MHz, CDCl3) h (ppm): -113.92. HRMS (ESI) m / z calculated value [C 14 H 25 [FO2SSi2] 332.1098, measured value 333.1166 (M+H).

[0089] Step 2: Synthesis of Compound 3

[0090] Compound 2 (4.0 g, 12 mmol) was dissolved in anhydrous tetrahydrofuran (200 mL), and TBAF (tetrabutylammonium fluoride) (14.4 mL, 14.4 mmol, 1.2 eq) was added dropwise. The mixture was stirred at room temperature for 2 hours, then the reaction mixture was quenched with 40 mL of H2O and extracted with CHCl3 (3 × 50 mL). The combined organic layers were washed with saturated NaHCO3 (aq, 20 mL) and H2O (40 mL), and then dried over anhydrous Na2SO4. After removing the solvent under vacuum, the residue was purified by silica gel column chromatography with PE:CHCl3 = 3:1 as the eluent to give compound 3 (2.02 g, yield = 89.4%) as a colorless liquid.

[0091] 1 H NMR (500MHz, CDCl3)h (ppm): 7.98 (t, J = 5.0Hz, 1H), 6.78 (s, 1H), 4.26-4.23 (m, 2H), 1.89-1.68 (m, 2H), 1.01 (m, 3H). 13 C NMR (126MHz, CDCl3)h (ppm): 160.92 (d, J = 5.0Hz, C = O), 157.63 (d, J = 279.6Hz, CF), 132 .40(d,J=3.78Hz),122.41(d,J=17.6Hz),105.36(d,J=21.4Hz),66.43,22.02,10.43. 19 F NMR (376MHz, CDCl3) h (ppm): -126.41. HRMS (ESI) m / z calculated value [C8H9FO2S] 188.0307, ​​measured value 189.0380 (M+H).

[0092] Step 3: Synthesis of Compound 4

[0093] Compound 3 (2.02 g, 10.7 mmol) was dissolved in anhydrous tetrahydrofuran (THF) (100 mL), and LiHMDS (14.2 mL, 12.8 mmol, 1.2 eq) was added dropwise at -78 °C. The reaction mixture was stirred at -78 °C for 1 hour, and BrCCl2CCl2Br (4.88 g, 15 mmol, 1.4 eq) in THF was added to the reaction mixture at -78 °C for 1 hour. The reaction mixture was then slowly heated to ambient temperature and stirred at this temperature overnight. The reaction mixture was quenched with 40 mL of H2O, extracted with CHCl3 (3 × 50 mL), and the combined organic layers were washed with saturated NaHCO3 (aq, 20 mL) and H2O (40 mL). The organic layers were dried on anhydrous Na2SO4. After removing the solvent under vacuum, the residue was purified by silica gel column chromatography, using PE:CHCl3 = 3:1 as the eluent to obtain compound 5 (1.8 g, yield = 63.3%).

[0094] 1 H NMR (400MHz, CDCl3)h (ppm): 6.74 (s, 1H), 4.27 (t, J = 4.0Hz, 2H), 1.80-1.73 (m, 2H), 1.02 (t, J = 8.0Hz, 3H). 13 C NMR (100MHz, CDCl3)h (ppm): 159.51 (d, J = 5.0Hz, C = O), 154.08 (d, J = 270Hz, CF), 1 22.25(d,J=33Hz),117.43(d,J=7.0Hz),91.90(d,J=23Hz),67.24,21.91,10.53. 19 F NMR (376MHz, CDCl3) h (ppm): -117.03. HRMS (ESI) m / z calculated value [C8H8BrFO2S] 265.9412, measured value 266.9478 (M+H).

[0095] Step 4: Synthesis of Compound 5

[0096] Compound 4 (0.53 g, 2 mmol) was dissolved in 10 mL of THF, and then NaOH (0.48 g, 12 mmol, 6.0 eq), 10 mL of EtOH, and 10 mL of H₂O were added to the solution. The mixture was refluxed overnight and then cooled to room temperature. The solvent was evaporated under reduced pressure, and the remaining solid was dissolved in 150 mL of H₂O and acidified with 6 M HCl. The resulting compound 5 (0.40 g, yield = 90%) was collected by filtration and can be used in the following reactions without further purification.

[0097] 1 H NMR (400MHz, DMSO-d6) δ12.95(s,1H),8.24(s,1H).

[0098] Step 5: Synthesis of Compound 6

[0099]

[0100] Compound 5 (2.0 g, 8.9 mmol), 2-butyloctyl-1-ol (1.99 g, 10.7 mmol), 4-(dimethylamino)pyridine (1.3 g, 10.7 mmol), and 1,3-dicyclohexylcarbodiimide (2.2 g, 10.7 mmol) were dissolved in toluene (150 mL) under argon atmosphere. The reaction mixture was stirred at 110 °C for 24 h. The reaction was then quenched with water and extracted three times with petroleum ether. The combined organic layers were dried over anhydrous Na₂SO₄ and concentrated under reduced pressure. The residue was purified by silica gel column chromatography using CH₂Cl₂:PE (1:3) as eluent to provide product compound 6 (2.83 g, yield = 81%).

[0101] 1 H NMR (400MHz, CDCl3) δ (ppm): 6.73 (d, J = 2.1Hz, 1H), 4.23-4.22 (d, J = 5.5Hz, 2H), 1.75-1.70 (m, 1H), 1.44-1.27 (m, 16), 0.91-0.85 (m, 6H). 13 C NMR (100MHz, CDCl3)δ (ppm)

[0102] 160.55 (d, J = 4.8 Hz), 156.31, 153.62, 121.88 (d, J = 18.8 Hz), 118.84 (d, J = 6.4 Hz), 105.26 (d, J = 24.3 Hz), 67.90, 37.25, 31.77, 31.16, 30.84, 29.56, 28.87, 26.63, 22.94, 22.62, 14.06 (d, J = 4.4 Hz). HRMS(ESI) m / z calculated values ​​[C 17 H 26 [BrFO2S] 392.0821, measured value 393.0887 [M+H] + .

[0103] Step 6: Synthesis of Compound 7

[0104]

[0105] Compound 6 (1.70 g, 4.3 mmol), (E)-1,2-bis(tributyltinyl)ethylene (1.21 g, 2.0 mmol), and Pd(PPh3)4 (115 mg, 0.1 mmol) were mixed in 20 mL of anhydrous toluene under argon atmosphere. The mixture was then stirred overnight at 110 °C. After cooling to room temperature, the crude product was concentrated under reduced pressure and further purified by silica gel column chromatography using CH2Cl2:PE (1:1) as eluent. Compound 7FETVT (1.03 g, yield: 79%) was finally obtained.

[0106] 1 H NMR (400MHz, CDCl3) δ (ppm): 8.05 (s, 1H), 6.65 (d, J = 1.4Hz, 1H), 4.24 (d, J = 5.5Hz, 2H), 1.77-1.74 (m, 1H), 1.41-1.26 (m, 16), 0.90-0.85 (m, 6H). 13 C NMR (100MHz, CDCl3) δ (ppm): 161.90 (d, J = 5.2Hz), 157.97, 155.29, 146.42, 123.66, 118.80 (d, J = 17.3Hz), 103.17 (d, J = 21.9Hz), 67.77, 37.32, 31.79, 31.21, 30.88, 29.58, 28.90, 26.67, 22.95, 22.63, 14.07 (d, J = 4.5Hz). HRMS (ESI) m / z calculated values ​​[C 36 H 54 F₂O₄S₂] 652.3432, measured value 653.3489 [M+H] + .

[0107] Step 7: Synthesis of Compound 8

[0108]

[0109] Compound 7FETVT (0.5 g, 0.77 mmol) and BrCCl2CCl2Br (0.35 g, 1.08 mmol) were dissolved in 100 mL THF. The reaction mixture was stirred at -78 °C for 10 min. Then, LiHMDS (0.92 mL, 1.0 M, 0.92 mmol, 1.2 eq) was added dropwise at -78 °C. The reaction mixture was stirred at -78 °C for 4 h. The reaction mixture was quenched with 40 mL H2O and extracted with CH2Cl2 (3 x 50 mL). The combined organic layers were then washed with saturated NaHCO3 aqueous solution (20 mL) and H2O (40 mL). The organic layers were dried over anhydrous Na2SO4. After removing the solvent under vacuum, the residue was purified by silica gel column chromatography using PE:CH2Cl = 1:1 as the eluent to give the monomer FETVT-Br (0.35 g, 56.3%) as a pale yellow solid.

[0110] 1 H NMR (400MHz, CDCl3) δ (ppm): 7.97 (s, 1H), 4.24-4.22 (d, J = 5.3Hz, 2H), 1.75-1.72 (m, 1H), 1.39-1.28 (m, 16), 0.90-0.86 (m, 6H). 13 C NMR (100MHz, CDCl3) δ (ppm): 160.92, 155.86, 153.17, 145.55, 123.21, 118.97 (d, J = 16.8Hz), 92.60 (d, J=23.9Hz),68.04,37.32,31.80,31.16,30.85,29.57,28.93,26.68,22.95,22.64,14.08(d,J=3.4Hz). 19 FNMR (376MHz, CDCl3) δ (ppm): -117.43. HRMS (ESI) m / z calculated value [C 36 H 52 [Br2F2O4S2] 808.1642, measured value 809.1677 [M+H] + .

[0111] The proton NMR spectrum, carbon NMR spectrum, fluorine NMR spectrum, and high-resolution mass spectrum of compounds 6, 7, and 8 are as follows: Figures 1-9 As shown.

[0112] Example 2

[0113] In this embodiment, the p-type organic semiconductor material PFETVT-T with the structure shown in Formula I is prepared through the following process:

[0114]

[0115] To a 5 mL reaction tube equipped with a stir bar, add monomer compound 8FETVT-Br (50 mg, 0.062 mmol), dimethyltinylated monomer 2,5-bis(trimethyltinyl)thiophene (25.3 mg, 0.062 mmol, 1.0 eq), Pd2(dba)3 (0.84 mg, 0.00093 mmol, 1.5% eq), P(o-tolyl)3 (2.25 mg, 0.0074 mmol, 12% eq), and anhydrous toluene (2.5 mL). The reaction tube was purged with argon and sealed under an argon flow.

[0116] The tube was then placed in a microwave reactor and heated to 140°C for 3 hours. After cooling to room temperature, the reaction solution was added dropwise to 80 mL of methanol and stirred for 1 hour. The precipitated solid was then filtered through a tube and Soxhlet extraction was performed using methanol, hexane, and dichloromethane as solvents to remove impurities and low molecular weight fractions. The residue was extracted with chloroform as the final solvent, the chloroform solution was concentrated to ~20 mL, and the precipitate was added to 100 mL of methanol. The precipitate was filtered and dried under vacuum to produce a product polymer (41 mg, 91%) as a deep blue solid. Due to the limited solubility of this polymer in various deuterium solvents, high-quality measurements were not possible. 1 HNMR spectrum. Molecular weight: Mn = 6.2 kDa, PDI = 1.8.

[0117] Example 3

[0118] In this embodiment, the p-type organic semiconductor material PETVT-FT with the structure shown in Formula I is prepared. The specific process is as follows:

[0119]

[0120] Compound 9 (0.206 g, 1 mmol), 2-butyloctyl-1-ol (0.219 g, 1.2 mmol), 4-(dimethylamino)pyridine (0.146 g, 1.2 mmol), and 1,3-dicyclohexylcarbodiimide (0.246 g, 1.2 mmol) were dissolved in toluene (20 mL) under argon atmosphere. The reaction mixture was stirred at 110 °C for 24 h. The reaction was then quenched with water and extracted three times with petroleum ether. The combined organic layers were dried over anhydrous Na₂SO₄ and concentrated under reduced pressure. The residue was purified by silica gel column chromatography using CH₂Cl₂:PE (1:3) as eluent to provide product compound 10. The product was used directly in the next reaction.

[0121]

[0122] Under argon atmosphere, a solution of compound 10 (1.62 g, 4.3 mmol), (E)-1,2-bis(tributyltin)ethylene (1.21 g, 2.0 mmol), and Pd(PPh3)4 (115 mg, 0.1 mmol) in 20 mL of anhydrous toluene was mixed. The mixture was then stirred overnight at 110 °C. After cooling to room temperature, the crude product was concentrated under reduced pressure and further purified by column chromatography on silica gel using CH2Cl2:PE (1:1) as the eluent. Finally, compound ETVT (1.0 g, yield = 82%) was obtained.

[0123] 1 H NMR (400MHz, CDCl3) δ (ppm): 8.19 (s, 1H), 7.44 (d, J = 5.4Hz, 1H), 7.13 (d, J = 5.3Hz, 1 H),4.22(d,J=5.6Hz,2H),1.77-1.74(m,1H),1.40-1.27(m,16),0.91-0.85(m,6H). 13 C NMR (100MHz, CDCl3) δ (ppm): 163.53, 148.54, 130.14, 129.23, 124.36, 123.32, 67.57, 37.42, 31.80, 31.45, 31.12, 29.61, 28.98, 26.74, 22.98, 22.64, 14.07, 14.05. HRMS (ESI) m / z calculated values ​​[C 36 H 54 [O4S2]616.3620, measured value 617.3672[M+H]+.

[0124]

[0125] Compound ETVT (1.05 g, 1.70 mmol) was dissolved in a mixed solvent of CHCl3 (50 mL) and trifluoroacetic acid (10 mL) at 0 °C and under light-shielding conditions. N-bromosuccinimide (NBS) (665 mg, 3.74 mmol) was then added to the solution in several portions. The reaction mixture was stirred overnight and poured into water. The organic layer was then concentrated by rotary evaporation. The residue was preliminarily purified by silica gel column chromatography using PE:CH2Cl2 (1:1) and then recrystallized from ethanol. The obtained compound ETVT-Br was a pale yellow solid (1.10 g, yield = 85%).

[0126] 1H NMR (400MHz, CDCl3) δ (ppm): 8.0 (s, 1H), 7.37 (s, 1H), 4.21 (d, J = 5.6Hz, 2H), 1.77-1.74 (m, 1H), 1.34-1.28 (m, 16), 0.92-0.86 (m, 6H). 13 C NMR (100MHz, CDCl3) δ (ppm): 163.53, 148.54, 130.14, 129.23, 124.36, 123.32, 67.57, 37.42, 31.80, 31.45, 31.12, 29.61, 28.98, 26.74, 22.98, 22.64, 14.07, 14.05. HRMS (ESI) m / z calculated values ​​[C 36 H 54 [Br2O4S2]772.1830, measured value 773.1883 [M+H]+.

[0127]

[0128] In a 5 mL reaction tube equipped with a stir bar, monomer ETVT-Br (50 mg, 0.065 mmol), distilled monomer (3,4-difluorothiophene-2,5-diyl)bis(trimethyltin) (28.8 mg, 0.065 mmol, 1.0 equivalent), Pd2(dba)3 (0.89 mg, 0.00098 mmol, 1.5% equivalent), P(o-tolyl)3 (2.36 mg, 0.0078 mmol, 12% equivalent), and anhydrous toluene (2.5 mL) were added. The reaction tube was purged with argon and sealed under an argon flow. The tube was then placed in a microwave reactor and heated to 140 °C for 3 hours. After cooling to room temperature, the reaction solution was added dropwise to 80 mL of methanol and stirred for 1 hour. The precipitated solid was then filtered through a sleeve and subjected to Soxhlet extraction using methanol, n-hexane, and dichloromethane as solvents to remove impurities and low molecular weight fractions. The residue was extracted with chloroform as the final solvent, the chloroform solution was concentrated to 20 mL, and the precipitate was added to 100 mL of methanol. The precipitate was filtered and dried under vacuum to give a polymer product (40 mg, 85%) as a dark blue solid. Due to the limited solubility of this polymer in various deuterated solvents, high-quality measurements were not possible. 1 1H NMR spectrum. Molecular weight. Mn = 71.9 kDa, PDI = 1.60.

[0129] Example 4

[0130] In this embodiment, following the aforementioned synthesis method, other polymers were synthesized according to the following reaction formulas:

[0131]

[0132]

[0133]

[0134] Experimental Example 1

[0135] In this embodiment, the polymers PFETVT-T and PETVT-FT were subjected to ultraviolet absorption spectroscopy, electrochemical testing, and thermal stability characterization.

[0136] UV-Vis absorption spectra and cyclic voltammetry of polymer PFETVT-T in solution and thin film states, as well as... Figure 10 and 11 As shown, the introduction of fluorinated esters effectively lowers the molecular orbital energy levels of polymer molecules (HOMO = -5.63 eV; LUMO = -3.18 eV). When applied in all-polymer solar cells, it provides better energy level matching and spectral complementarity with the polymer acceptor, which is beneficial for photon absorption and increased current. Furthermore, as... Figure 12 As shown, the decomposition temperatures (T0) of PFETVT-T and PETVT-FT at 5% weight loss are... d The temperatures were 313℃ and 346℃, respectively, which means that these two PT-based polymers have good thermal stability in device fabrication and practical applications.

[0137] Experimental Example 2

[0138] This embodiment characterizes the morphology of polymers PFETVT-T and PETVT-FT.

[0139] Atomic force electron microscopy of polymers PFETVT-T and PETVT-FT, such as Figure 13 As shown, compared with monothiophene with only ester substitution, the introduction of fluoroester-substituted monothiophene effectively improved the crystallinity of the blend film. Transmission electron microscopy of the blend film of polymer donor PFETVT-T and polymer acceptor L15 is shown in the figure. Figure 13 This indicates that the PFETVT-T:L15 blend film exhibits a uniform nanoscale phase separation microstructure, which is beneficial for exciton separation and charge transport.

[0140] Example 5

[0141] Fabrication and characterization of solar cell devices

[0142] Bulk heterojunction all-polymer solar cells were constructed using PFETVT-T and PETVT-FT as polymer donor materials and L15 as polymer acceptor material, respectively. The active layer ratio was optimized to be 1:1 for polymer donor to polymer acceptor. Figure 14The figures show the current-voltage curves. The polymer PFETVT-T exhibits excellent photoelectric conversion efficiency, with a maximum PCE (photoelectric conversion efficiency) of 11.81%, the highest reported record for all-polymer solar cells based on polythiophene derivatives. This indicates that PFETVT-T is a promising donor material. In contrast, solar cells using an F-atom-free analog (PETVT-FT) as the polymer donor only achieved a PCE of 1.92%. Compared to ester-substituted monothiophene, the introduction of fluorinated ester-substituted monothiophene effectively improved the crystallinity of the blend film. This demonstrates that the introduction of fluorinated ester-substituted monothiophene effectively modulates the photoelectric properties of the polymer molecules and is an effective strategy for constructing high-performance photovoltaic materials based on polythiophene ethylene derivatives.

[0143] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, modifications, substitutions, combinations, or simplifications made without departing from the spirit and principle of the present invention shall be considered equivalent substitutions and shall be included within the protection scope of the present invention.

Claims

1. A polymer of formula I: Formula I in, R is selected from m is selected from natural numbers between 1 and 20; Dashed lines indicate connection points; Includes π-conjugated structural groups; X is selected from halogen atoms; n is a natural number between 100 and 3000; The π-conjugated structural group is selected from any one of the following groups: R1 is selected from hydrogen atoms and alkyl groups; the dashed line indicates the connection position.

2. A polymer, characterized in that: The polymer is selected from any of the following: , , , , , , ; n is a natural number between 100 and 3000; Dashed lines and wavy lines indicate connection points.

3. A method for preparing the polymer of formula I as described in claim 1, characterized in that: Includes the following steps: Polymer of formula I was prepared by Stille coupling polycondensation of compound Ih and compound Ii. Among them, R, X, The definitions of n are as described in claim 1.

4. A thin-film semiconductor, characterized in that: Includes the polymer of formula I as described in claim 1.

5. A composite, characterized in that: Includes a substrate and a thin-film semiconductor as described in claim 4 deposited on the substrate.

6. A field-effect transistor device, characterized in that: Includes the thin-film semiconductor as described in claim 4 or the composite as described in claim 5.

7. A photovoltaic device, characterized in that: Includes the thin-film semiconductor as described in claim 4 or the composite as described in claim 5.

8. An organic light-emitting device, characterized in that: Includes the thin-film semiconductor as described in claim 4 or the composite as described in claim 5.

Citation Information

Patent Citations

  • Semiconductor materials prepared from dithienylvinylene copolymers

    CN102317345A